On the use of immune checkpoint inhibitors in patients with viral infections including COVID-19. Issue 2 (1st July 2020) - Gambichler, Thilo; Reuther, Judith; Scheel, Christina H; Becker, Jürgen Christian
Abstract : The present review summarizes up-to-date evidence addressing the frequently discussed clinical controversies regarding the use of immune checkpoint inhibitors (ICIs) in cancer patients with viral infections, including AIDS, hepatitis B and C, progressive multifocal leukoencephalopathy, influenza, and COVID-19. In detail, we provide available information on (1) safety regarding the risk of new infections, (2) effects on the outcome of pre-existing infections, (3) whether immunosuppressive drugs used to treat ICI-related adverse events affect the risk of infection or virulence of pre-existing infections, (4) whether the use of vaccines in ICI-treated patients is considered safe, and (5) whether there are beneficial effects of ICIs that even qualify them as a therapeutic approach for these viral infections.